In vitro germination of Podophyllum hexandrum seeds. - Silva, Cláudia Gontijo; Davey, Michael Raymond; Power, John Brian; Shaw, Julian Mark Hugh (Ornamental Horticulture, 2007)
Considerable interest has centred on the Podophyllum-based lignans as lead compounds for the development of new drugs. The successful introduction of the anticancer drugs etoposide® and teniposide® and the development of new derivatives such as etopophos® have created a demand for podophyllotoxin. Currently it is obtained from the rhizomes and roots of wild populations of Podophyllum hexandrum, and thus the availability of this natural product is limited. There is an urgent need for a maintainable supply of P. hexandrum plants, a rare and threatened species. In the present work, a protocol was developed for the sterilisation and germination of seeds of P. hexandrum. Ripe fruits were harvested from seed-derived plants cultivated at the University of Nottingham. Seeds were removed from fruits, left for 20 – 30 min in running water, and washed three times with sterile, reverseosmosis water. Seeds were surface sterilised in (5, 10, 15 and 20%; v:v) Domestos bleach solution with 0.2% (v:v) Tween 20 for 5, 10, 15 and 20 min, followed by three washes in sterile, reverse-osmosis water. The effect of storage as a pre-treatment for the germination of seeds was also investigated. Sterilised seeds were kept in Petri dishes and maintained in the dark at 22 ± 1°C for 30 d. Ten stored seeds were cultured per dish containing a moist sterile filter paper disk. Cultures were incubated in the dark (22 ± 1 °C). Seeds with emerged radicles were individually transferred onto full-strength MS medium containing IAA (0.00875 mg l-1) in combination with kinetin (0.03 mg l-1) and folic acid (0.01 mg l-1) designated BGS medium. Seeds were also transferred onto full-strength MS medium lacking growth regulators (MSO medium). Media were supplemented with 3.0% (v:v) sucrose and solidified with 0.8% (w:v) agar. Cultures were maintained under diffuse light (3.8 µmol m-2 s-1) at 22 ± 1°C for three weeks and then transferred to a 16 h photoperiod under fluorescent light (42 µmol m-2 s-1) at 22 ± 1°C. Seed sterilisation was best achieved with 20% (v:v) Domestos and 0.2% (v:v) Tween 20 for 20 min. The results from these studies confirm that a post-harvest ripening period of 30 d was required for in vitro seed germination. If seeds are stored in moist and dark conditions, spontaneous germination occurs within 35 to 40 d. Axenic cultures were successfully established either on full-strength BGS medium with growth regulators or fullstrength MS medium lacking growth regulators. However, the overall growth of plants showing a normal morphology was superior on the latter medium. The in vitro-grown seedlings can be used as an alternative source of plant material for tissue culture experiments.